2016
DOI: 10.1007/s00383-016-3896-z
|View full text |Cite
|
Sign up to set email alerts
|

Staged imaging pathway for the evaluation of pediatric appendicitis

Abstract: The staged imaging pathway resulted in a marked decrease in children exposed to CT without compromising diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…They observed that, while US use appeared to be increasing and CT use decreasing, the proportion of patients experiencing appendiceal perforation did not change substantially. Similarly, after implementation of a staged US-first pathway for pediatric patients evaluated for appendicitis in a community, nonacademic hospital, Chien et al 10 found a decrease in CT usage but no statistical difference in perforation rate between the 12 months pre-and post-intervention. Additionally, Aspelun et al 11 retrospectively compared a CT pathway with an US-followed-by-MRI pathway in children with suspected appendicitis, each over a two-year period, and similarly found that there was no statistical difference in perforation rate.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They observed that, while US use appeared to be increasing and CT use decreasing, the proportion of patients experiencing appendiceal perforation did not change substantially. Similarly, after implementation of a staged US-first pathway for pediatric patients evaluated for appendicitis in a community, nonacademic hospital, Chien et al 10 found a decrease in CT usage but no statistical difference in perforation rate between the 12 months pre-and post-intervention. Additionally, Aspelun et al 11 retrospectively compared a CT pathway with an US-followed-by-MRI pathway in children with suspected appendicitis, each over a two-year period, and similarly found that there was no statistical difference in perforation rate.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, after implementation of a staged US-first pathway for pediatric patients evaluated for appendicitis in a community, non-academic hospital, Chien et al. 10 found a decrease in CT usage but no statistical difference in perforation rate between the 12 months pre- and post-intervention. Additionally, Aspelun et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been several reports of clinical pathways aimed at reducing the use of CT scans in children with suspected appendicitis, many with varying success. [8][9][10][11][12][13][14][15][16] A single-center study of 1886 patients compared the use of CT scans before and after the implementation of a diagnostic pathway that incorporated risk profiles based on pediatric appendicitis score and US findings. This resulted in a decrease in CT scans in the moderate risk (22.3% versus 12.2%) and high-risk groups (25.2% versus 14.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CT scan rates decreased from 91.7% to 25.1%. 8 Another study of 1397 patients demonstrated that implementing a diagnostic pathway using a clinical scoring system and surgical consultation to encourage US use before CT scan resulted in a reduction of CT scans from 75% to 24%. 12 To our knowledge, the present study is the first to incorporate risk profiles based on the combined predictive value of laboratory and US data together into a diagnostic pathway for suspected appendicitis.…”
Section: Discussionmentioning
confidence: 99%